The phase-space approach to time evolution of quantum states in confined systems: The spectral split-operator method - Kołaczek, Damian; Spisak, Bartłomiej J.; Wołoszyn, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
Using the phase space approach, we consider the quantum dynamics of a wave packet in an isolated confined system with three different potential energy profiles. We solve the Moyal equation of motion for the Wigner function with the highly efficient spectral split-operator method. The main aim of this study is to compare the accuracy of the employed algorithm through analysis of the total energy expectation value, in terms of deviation from its exact value. This comparison is performed for the second and fourth order factorizations of the time evolution operator.
Keywords: Wigner distribution function; Moyal dynamics; spectral split-operator method